Trends in functional programming : 21st International Symposium, TFP 2020, Krakow, Poland, February 13-14, 2020, Revised selected papers /: 21st International Symposium, TFP 2020, Krakow, Poland, February 13-14, 2020, Revised selected papers. (2020) - Unknown
No abstract available